Effects of pasteurization and storage time on watermelon juice quality enriched with L-citrulline (2017)
Watermelon juice has gained increasing popularity among consumers as a rich natural source of functional compounds such as lycopene and L-citrulline. This amino acid is an excellent candidate to reduce muscle soreness. Watermelon juice enriched with L-citrulline is presented as an industry opportunity for the sport drink sector. However, the application of conventional thermal pasteurization can degrade those functional compounds. Effects of pasteurization at 80°C for 40 s (PW-40 s) or 90 s (PW-90 s) and storage (4°C for 30 days) on watermelon juice enriched with Lcitrulline was studied. Before pasteurization, initial lycopene content was 14.65±0.30 mg kg-1, reducing to 10.50±0.06 in PW-40 s and 10.10±0.08 mg kg-1 in PW-90 s after 30 days. Initial enriched L-citrulline content was 15.68±0.05 g L-1 that decreased to 12.38±0.03 in PW-40 s and 12.04±0.09 g kg-1 in PW-90 s treatment after 30 days of storage. Pathogenic bacteria (Salmonella spp., Listeria monocytogenes and Escherichia coli) were not detected during storage. However, mesophilic growth was high, reaching 7.5 log cfu mL-1 in PW-40 s and 6.5 log cfu mL-1 in PW-90 s. The appearance limited the shelf life to 25 days for PW-40 s and only 15 days for PW-90 s. The use of higher temperatures of pasteurization is necessary to obtain a safe watermelon juice, but this needs to be balanced with reduced treatment times to maintain functional and sensory parameters which are easily thermo-degraded.